Facile and cost-effective synthesis of CNT@MCo2O4 (M = Ni, Mn, Cu, Zn) core–shell hybrid nanostructures for organic dye removal1. Issue 97 (21st October 2015) - Li, Haizhen; Sun, Zebin; Tian, Yaxi; Cui, Guijia; Yan, Shiqiang
<x xml:space="preserve">Abstract</x> This study presents four hybrid materials of CNT@MCo2O4 (M = Ni, Mn, Cu, Zn) which were prepared via a simple chemical bath deposition method at room temperature followed by a post-annealing treatment.